Communicative Methodology of Teaching Russian in Higher Education (Journal of Pedagogical Inventions and Practices, 2022)
The communicative direction in the teaching of Russian language is characterized by the fact that it is in the foreground as the most important. The purpose of the study is the formation of skills and oral communication. experience, the process of acquiring knowledge about the process of language and language acquisition.